Optimal control of unknown nonaffine nonlinear discrete-time systems based on adaptive dynamic programming - Wang, Ding; Liu, Derong; Wei, Qinglai; Zhao, Dongbin; Jin, Ning (Automatica (Oxford), 2012)
An intelligent-optimal control scheme for unknown nonaffine nonlinear discrete-time systems with discount factor in the cost function is developed in this paper. The iterative adaptive dynamic programming algorithm is introduced to solve the optimal control problem with convergence analysis. Then, the implementation of the iterative algorithm via globalized dual heuristic programming technique is presented by using three neural networks, which will approximate at each iteration the cost function, the control law, and the unknown nonlinear system, respectively. In addition, two simulation examples are provided to verify the effectiveness of the developed optimal control approach.